Design of ultra-precision piston/cylinders for directly calibrated hydraulic amplification - Dennis, Ashley Grant (Cranfield University, 2022)
Force calibrations in the Mega Newton range are not currently providing the accuracy required by industry. This work addresses a hydraulic force standards, which perform such calibrations, which work b amplifying the force produced on a small piston/cylinder assembly (PCA) by connecting it hydraulically to a larger PCA. The force standards are currently calibrated using a transducer to the more accurate deadweight machines, but not without a resulting uncertainty of 0.01 % - 0.02 % imparted by the transducer performing the calibration. Because of this, the potential for evaluating uncertainties within the machine from first principles and using it as a primary machine, with traceability maintained to the weights is evaluated. First of all the potential for the resulting reduction in uncertainties is evaluated analytically, then FEA/CFD work is carried out to produce analytical formulae which allow for the design of a directly calibrated system. The analysis is carried out for both the rotational and non-rotational variants of PCA. Finally, the design of a primary hydraulic standard is carried out using FEA/CFD.
Keywords: Force Metrology; Mega Newton; Pressure Balance; Direct Calibration; Primary Standard; FEA; CFD